Using the Dermatology Life Quality Index to Assess How Breast Radiodermatitis Affects Patients' Quality of Life. (April 2019) - Beamer, Laura Curr; Grant, Marcia
Purpose: The purpose of this study is to report the initial validation process for using the Dermatology Life Quality Index (DLQI) for radiodermatitis of the breast. Methods: This is an additional analysis of a study designed to report a longitudinal study in skin-related and global quality of life in women with breast radiodermatitis. A total of 40 participants completed the DLQI instrument weekly while receiving external radiotherapy of the female breast. At week 5 on treatment, 31 (78%) participants provided narrative feedback on how each DLQI item affected her life. Agreement between participant DLQI numerical ratings and narrative feedback on items was assessed. Construct validity was estimated using principal component analysis (PCA). Internal consistency of the DLQI was assessed using Cronbach alpha. Results: Percentage of agreement between participant DLQI ratings and narratives ranged from 71% to 98%. Each participant responded "no" to the work and study item leading to zero variance and removal from our analyses. Principal component analysis supported the inclusion of all of the remaining items. The DLQI with nine remaining items demonstrated moderately good internal consistency (α = .69). Conclusions: The results of our examination of the DLQI when used for breast radiodermatitis are promising. Next steps include additional larger studies among more diverse populations.